Assembleia escolar estudantil: espaço para produção de diários reflexivos - Silva, Roksyvan de Paiva (2020)
Each individual specimen of the human species is by nature social, and this essential predicate manifests itself when speaking, listening, reading and writing. However, the school, which is responsible for developing human capacities, in addition to being a citizen, is often based on silence. Following the opposite path, that leads to the shouting, this research sought to analyze how pedagogical work through the student school assembly can contribute to the development of reflective diary writing. The main subjects were seventh grade students from a public school in João Pessoa, PB. The study revolved around the gnosio-epistemic pattern of scientificity, acquiring qualitative features and interventional nature, which brought the fieldwork closer to the milestones of an action research. The course of investigation was based, on the functioning of student school assemblies, on the ideas of Freinet (1973, 1976), Puig et al. (2000) and Araújo (2004); and regarding the comprehension of the discursive genres assembly and reflective diary, in the works of Bakhtin (2010), Marcuschi (2008, 2010), Kleiman (1995), Zabalza (2004) and Reichmann (2013). During the teaching intervention in the students' written production, Serafini (1989) and Ruiz (2010), as well as the curricular guidelines contained in the PCN and BNCC (BRASIL, 1998; 2018), served as a parameter and guide. The generation of data was done in the classroom with textual production, audio recordings, holding of student school assemblies and conversation circles, in addition to participant observation. From the information generated, the resulting corpus was composed mainly of the students‘ reflective diaries and, secondarily, the audio transcripts, agendas and minutes of the assemblies, as well as passages from my own field diary. The reflective diaries written by the students were subjected to examination according to the content analysis procedures and techniques. In this analytical step, we selected the theme as the record unit and the verbal interactions of the student school assembly as the context unit, according to the studies by Franco (2007) and Bardin (1979). The inference and categorization operations incident on the corpus led to the interpretation that the student assemblies contribute to develop in the student an autonomous, critical and participatory activity, neutralizing forms of violence and proposing conflict resolution through dialogue. The written production of the diaries reflected, in turn, the context of the debates and clashes held in the assemblies, revealing in this other modality of language previously ignored individuals, to develop a parallel and underground but intense activity of reflection about themselves and the world.